Development of Pop-Up Book ‘Ayo Siaga Bencana’ to Cultivate Disaster Mitigation Awareness in Early Childhood - Khoirunnisa, Dyah; Lilis Suryani; Irma Yuliantina (UNIB Press, 2025)
This study aims to develop the Pop Up Book media